Growth performances , carcasses parameters and meat fatty acid composition of lamb fed green oak acorns ( Quercus ilex ) based diet - Keddam, Ramdane; Bouderoua, Kaddour; El-affifi, Mohamed; Attou, Ghalem Selselet- (African Journal of Biotechnology, 2010)
The aim of this experiment is to compare the effects of diets containing green oak acorns (GO) and barley (BL) on the growth performances, carcasses parameters and the composition in fatty acids of lambs. Two groups of five lambs each were fed, respectively, during 105 days with diets containing 50% of oaks acorns and 50% of barley. At the end of the test, the animals of the two diets expressed comparable body weights and weight gain. A significant difference (P < 0.05) was observed for the thickness of fat cover which is 3 mm for the BL group against 1.6 mm for GO group even if no significant difference was revealed concerning the output with slaughtering. The intramuscular lipids were significantly higher (P < 0.05) in the group of animals fed with GO diet compared to the BL diet (3.88 vs 2.83 g.100-1 g of muscle). Among the saturated fatty acids (SFA), the stearic acid significantly appeared in higher proportion (P < 0.05) in GO diet (20.8 vs 18.1%) whereas the palmitic acid is prevalent in the group of animals fed with the BL diet (25 vs 30%). For the polyunsaturated fatty acid (PUFA), no significant difference was observed between the two groups. The linoleic acid is prevalent among the PUFA of two groups without significant difference. The linolenic acid is higher in the animal fed BL. The n-6: n-3 ratio is higher in the BL group (8.9 vs 7.3). At the end, the low level of incorporation of PUFA in muscle of the lamb because of biohydrogenation, suggests us supplementing the diet by green grass.
Keywords: barley; fatty acid; lamb; meat; oak acorn